1998
DOI: 10.1056/nejm199807303390502
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate for the Prevention and Treatment of Glucocorticoid-Induced Osteoporosis

Abstract: Alendronate increases bone density in patients receiving glucocorticoid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
392
0
35

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,150 publications
(446 citation statements)
references
References 27 publications
19
392
0
35
Order By: Relevance
“…Thus, the use of RANKL antagonist in XHIM patients may lead to an increased predisposition to infection. Oral bisphosphonates target osteoclast-mediated bone loss, and they have been shown to enhance bone mineralization in adults (33,34). Although the majority of XHIM patients are children, and well controlled studies using bisphosphonates in younger patients are lacking, this class of drugs could be of value for some XHIM patients with marked bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of RANKL antagonist in XHIM patients may lead to an increased predisposition to infection. Oral bisphosphonates target osteoclast-mediated bone loss, and they have been shown to enhance bone mineralization in adults (33,34). Although the majority of XHIM patients are children, and well controlled studies using bisphosphonates in younger patients are lacking, this class of drugs could be of value for some XHIM patients with marked bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…22) Bisphosphonates have also been found to be eŠective against glucocorticoid-induced osteoporosis in randomized, placebo-controlled clinical studies. 23,24) Guidelines put out by the UK Consensus Group made bisphosphonates theˆrst choice for treatment of glucocorticoid-induced osteoporosis. 3) Although the number of patients in this study was very small and therefore the statistical power was limited, treatment by bisphosphonate was thought to be one of the eŠective methods.…”
Section: Discussionmentioning
confidence: 99%
“…53,55,57,60,61,64,65,67,68,71,76,84,91,93 Two of these RCTs also included an evaluation of other doses of alendronic acid not currently licensed. 76,91,98 Two of the RCTs in postmenopausal women reported that participants were switched from a 5 mg daily dose of oral alendronic acid to 10 mg per day after 24 months, spending the remaining 12 months of the RCT on 10 mg per day.…”
Section: Study and Population Characteristics Of Included Trialsmentioning
confidence: 99%